OPPORTUNITIES AND WAYS TO IMPLEMENT THE HISTORICAL MATERIAL IN TEACHING ORGANIC CHEMISTRY (ResearchJet Journal of Analysis and Inventions, 2023)
This article describes the lives of great chemical scientists in teaching organic chemistry, their contributions to chemistry, their research work, their chemical experiments and their achievements in this field.